VALIDACIÓN DE UN PROGRAMA INFORMÁTICO PARA DETECCIÓN DE LA DESNUTRICIÓN HOSPITALARIA Y ANÁLISIS DEL COSTE HOSPITALARIO. - Fernández Valdivia, Antonia; Rodríguez Rodríguez, José María; Valero Aguilera, Beatriz; Lobo Támer, Gabriela; Pérez de la Cruz, Antonio Jesús; García Larios, José Vicente (Nutrición Hospitalaria, 2015)
Background: one of the methods of diagnosis of malnutrition is serum albumin, for the simplicity of its determination and low cost.Objectives: the main objective is to validate and implement a computer program based on the determination of serum albumin, allowing early detection and treatment to malnourished or at risk of malnutrition patients, still another objective evaluation of costs by diagnosis-related groups.Methods: the study design is cohort, dynamic and prospective, which are included hospital discharge from november 2012 until march 2014, being the study population of patients over age 14 who enter the various services of a Medical Surgical Hospital of the Granada's Hospital Complex Univesity, whose numbers are lower serum albumin 3.5 g/dL, for a total of 307 patients.Results: of the 307 patients, 141 are malnourished (program sensitivity: 45.9%). 54.7% of patients were male and 45.3% female. The mean age of 65.68 years. The median length of stay is 16 days. 13.4% of patients have died. The average cost of GRD is € 5 958.30 and said average cost after detecting malnutrition is € 11 376.48.Conclusions: the algorithm that implements the software identifies nearly half of patients hospitalized malnourished. It is essential to record the diagnosis of malnutrition.